URGENSI PENDIDIKAN AGAMA HINDU BAGI ANAK - Armini, Ida Ayu Adi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Education is an effort to realize the growth of the character of the child (inner strength, character, mind or intellect) and the child’s body to refer to the child’s life in harmony with his world. But in the present era that is full of things that degrade the side of humanism. Education should give birth to the children who have good character, just the contrary gave birth to people who behave badly. Psychological touch is rarely found in education today. It is rooted in the application of education in which there are models and processes without touching the side of humanism itself, so the application of education is only a mere formality. Consequently, children were born intelligently good but spiritually less. Many children are smart, but few have good character. This is where the importance of religious education as a role synergized.